Experimental study on the processes and influencing factors of coal pillar damage under immersion conditions - Yuan, Huiqing; Xu, Zhimin; Sun, Yajun; Lu, Weining; Han, Yuhang; Xu, Xiangyu (Geosciences journal (Seoul, Korea), 2025)
After mining, the abandoned underground space accumulates acidic mine water with high permeability and strong corrosivity, damaging the structure of adjacent boundary coal pillars and reducing their mechanical strength and water resistance, which can lead to water inrush disasters. This study investigates the damage effects and influencing factors on boundary coal pillars under various immersion conditions, using on-site coal samples and a self-developed high-pressure mine water–rock coupling test device for simulation tests under different pressures and solutions. This study defines the ratio of the reduced mechanical strength of the immersed rock to that in its dry state as the “damage coefficient”. Results indicate significant damage to coal samples after 40 days of immersion, with damage coefficients for compressive, tensile, and shear strengths exceeding 0.3. Notably, the tensile strength of the #2 coal sample in acidic solution showed the most pronounced damage effect, reaching a maximum of 0.74. Structural damage is evident, characterized by a rough surface and increased internal micro-cracks. Key influencing factors include the hydrochemical characteristics of the immersion solution, immersion time, and the physical properties of the coal samples. These findings provide a theoretical basis and reference for optimizing the design and stability evaluation of water-proof coal pillars in production mines.